Strandings, bycatches and injuries of aquatic mammals in China, 2000–2006, as reviewed from official documents: A compelling argument for a nationwide strandings programme. (January 2015) - Wang, Yamin; Li, Wei; Van Waerebeek, Koen
Abstract: In the present study, the species composition, geographical and seasonal patterns of strandings, bycatches and injuries of aquatic mammals reported in Chinese mainland waters, from 2000 to 2006, were analyzed based on national official documents. A total of 97 strandings, 66 bycatches and 30 injuries, involving at least 18 species (possibly 20) in eight families of Cetacea and two families of Carnivora, were recorded. Finless porpoises (Neophocaena spp.), spotted seal ( Phoca largha) and bottlenose dolphins ( Tursiops spp. ) were the most common species in all three categories, in total comprising 59.8% of strandings, 97.0% of bycatches and 86.7% of injuries. Strandings occurred throughout the year, but records of both bycatches and injuries peaked in spring (March to May), corresponding to the major fishing season and may reflect the negative impacts of fishing activities. The highest species diversity found in Fujian Province may be linked to upwelling and high production in the Strait of Taiwan. Serious difficulties were encountered in overall data interpretation and between-provinces comparability, mainly due to a lack of quantified observer effort and variable expertise levels. Hence the establishment of a coordinated nationwide network is recommended, providing a mechanism for the instant reporting of aquatic mammal events, as well as the adoption of a standardised data recording system including necropsy protocols. Better-quality data should allow quantitative analyses leading to an improved understanding of anthropogenic threats in China׳s aquatic mammal populations. The need to upgrade reserve management, such as the Dalian protected area in Liaoning, is also stressed.